Economic impact of peste des petits ruminants on small ruminant production in Senegal: Gender considerations within a system dynamics modelling approach - Aboah, Joshua; Campbell, Zoë A.; Dione, Michel M.; Kotchofa, Pacem; Ilboudo, Guy S.; Wieland, Barbara; Lo, M.M.; Rich, Karl M. (Elsevier, 2024)
CONTEXT Peste des petits ruminants (PPR) remains a persistent challenge for small ruminant production in Senegal, leading to economic losses for livestock keepers. Gender dynamics and socio-cultural factors influence production decisions at the household level. Despite its relevance, economic impact models of PPR have not incorporated gender dynamics.